Urgensi Hakim Pemeriksaan Pendahuluan dalam Peradilan Pidana di Indonesia - Vega Christian Pratama; Louis Tappangan (Mahesa Research Center, 2020)
This article aims to analyze the importance of the preliminary supervisory judges stipulated in the Draft Criminal Procedure Code to replace pretrial institutions regulated in the Criminal Procedure Code in the future. As for the preliminary Supervisory Judge, it was formed with the aim of improving pretrial institutions which are deemed not running properly at this time. The problem focuses on the legal consequences of the use of violence by the investigator against the suspect or witness and the importance of the Preliminary Examination Judge to be applied to criminal justice in Indonesia to address the problem of the use of force by investigators. In order to answer this problem, a theoretical reference is used that applies to the process of proof in criminal procedural law and uses a microeconomic analysis of criminal law to analyze how important the enforcement of the Preliminary Examination Judge in Indonesia is. The research method used in this article is the statue approach and conceptual approach. This study concludes that the enforcement of Preliminary Examination Judges needs to be reviewed again, because there are still many deficiencies contained in the Draft KUHAP which regulates Preliminary Examination Judges. Although on the one hand the Preliminary Examination Judge is very much needed to overcome the problem of violence by investigators in the investigation, on the other hand there are other things that need to be reviewed so that criminal justice in Indonesia can be better in the future.